2015
DOI: 10.1016/j.rmed.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Lung function impairment increases with age of diagnosis in adult onset asthma

Abstract: Asthma was diagnosed as frequently in older as in younger adults. Preexisting symptoms were equally common, but lung function was more reduced pre-diagnosis, and declined more rapidly in older adults. This emphasizes the need for a high level of therapeutic attention in patients with asthma diagnosed late in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
2
25
0
1
Order By: Relevance
“…This is exactly the same number as was found in the Copenhagen City Heart Study. [23] The lung function in these patients is also similar to that found in the study by Porsbjerg et al,[23] i.e. about 80%.…”
Section: Discussionsupporting
confidence: 88%
“…This is exactly the same number as was found in the Copenhagen City Heart Study. [23] The lung function in these patients is also similar to that found in the study by Porsbjerg et al,[23] i.e. about 80%.…”
Section: Discussionsupporting
confidence: 88%
“…43 In that study, the proportion of newly diagnosed asthma was same in all the age groups: 7% at age >64 years, 7% at age 35-64 years and 6% at age <35 years. 43 As early as 1999, Davies et al reported a correlation between DL CO and response to ICS in COPD. 44 We believe that CT scan and KCO are the ideal techniques for phenotyping.…”
Section: Discussionmentioning
confidence: 70%
“…The Copenhagen City Heart Study reported on newly diagnosed asthma during a 10‐year follow‐up in a sample comprising 4983 individuals . In that study, the proportion of newly diagnosed asthma was same in all the age groups: 7% at age >64 years, 7% at age 35–64 years and 6% at age <35 years …”
Section: Discussionmentioning
confidence: 99%
“…Late onset, highlighted as a risk factor for accelerated decline by some authors, was not confirmed by our analysis. These inconsistencies can be explained by the difference in late onset definition varying from 18 years old to an onset during the time of study [9,12,50] or the possible misclassification of asthmatics in these studies due to self-reported diagnostic [9,12].…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, not all asthma patients decline over time, some show stable lung function and some others can outgrow their asthma disease [5]. Previous studies have revealed risk factors for accelerated FEV 1 decline in asthma: low baseline lung function (FEV 1 % predicted) [6,7], airway hyper-responsiveness [8], male gender [9], cigarette smoking [10,11], late asthma onset [12], duration of disease [4], frequent and severe exacerbations [13]. Moreover, the role of inflammation and eosinophilia in lung function decline has been highlighted with high eosinophil sputum numbers [5], high variability in sputum eosinophils [14], as well as higher blood eosinophil numbers [15] linked to accelerated rate of lung function decline in asthma.…”
Section: Introductionmentioning
confidence: 99%